2011
DOI: 10.1039/c1cc11877c
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial graphene polymer (PVK-GO) nanocomposite films

Abstract: The first report on the fabrication and application of a nanocomposite containing poly-N-vinyl carbazole (PVK) polymer and graphene oxide (GO) as an antimicrobial film was demonstrated. The antimicrobial film was 90% more effective in preventing bacterial colonization relative to the unmodified surface. More importantly, the nanocomposite thin film showed higher bacterial toxicity than pure GO-modified surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(113 citation statements)
references
References 31 publications
4
109
0
Order By: Relevance
“…The antibacterial activity of graphene and graphene oxide is widely documented and has already been utilized to create antibacterial materials for specific applications [15,16,19,30,31,32,33]. Liu et al compared the antibacterial activity of graphite, graphite oxide, graphene oxide (GO) and reduced graphene oxide (rGO), showing that GO and rGO are both strongly antibacterial (Figure 2) [34].…”
Section: Inherent Antibacterial Properties Of Carbon Nanomaterialsmentioning
confidence: 99%
“…The antibacterial activity of graphene and graphene oxide is widely documented and has already been utilized to create antibacterial materials for specific applications [15,16,19,30,31,32,33]. Liu et al compared the antibacterial activity of graphite, graphite oxide, graphene oxide (GO) and reduced graphene oxide (rGO), showing that GO and rGO are both strongly antibacterial (Figure 2) [34].…”
Section: Inherent Antibacterial Properties Of Carbon Nanomaterialsmentioning
confidence: 99%
“…The most common bacteria under investigation are E. coli and S. aureus . To this moment, no consensus has been reached regarding the antibacterial activity of graphene or graphene-derivative surfaces, but available data suggests that cytotoxicity against bacterial cells varies to some extent on the orientation of the surface particles, a result of the production method used [50, 51, 54, 55, 102]. Another factor altering the antibacterial effect of graphene and its derivatives is the quality of the material.…”
Section: Discussionmentioning
confidence: 99%
“…Lactoferrin and chitosan on a GO or r-Go composite film showed significant cytotoxicity against E. coli [53]. Other studies exist involving GO composite sheets with attached polyvinyl-N-carbazole, a polymer with antibacterial characteristics [54, 55]. The antibacterial activity of GO-polyvinyl-N-carbazole against E. coli, C. metallidurans , B. subtilis , and R. opacus was reported to be higher than the activity of unmodified GO surfaces, especially against Gram-positive bacteria.…”
Section: Special Characteristics Of Graphenementioning
confidence: 99%
“…Akhavan et al discovered GO as an excellent antimicrobial material for surface coatings . Santos et al first reported the fabrication and application of a nanocomposite containing GO that this antimicrobial film was 90% more effective in preventing bacterial colonization relative to the unmodified surface . Li et al demonstrated that coating of catheter and glass surfaces with hydrate GO (hGO) is capable of killing drug‐resistant bacteria (Fig.…”
Section: Antimicrobial Strategies For Urinary Cathetersmentioning
confidence: 99%